2013
DOI: 10.1111/scs.12073
|View full text |Cite
|
Sign up to set email alerts
|

Individual and organisational factors influencing registered nurses’ attitudes towards patient advocacy in Swedish community health care of elders

Abstract: Although the mentioned individual factors may be intertwined, the conclusion is that both individual and organisational factors influenced RNs' attitudes towards patient advocacy. The results do not verify that nursing experience, workplace experience, educational level or personality traits influence the RNs' attitudes towards patient advocacy. The proportion of explained variance indicates that additional factors also influence attitudes towards patient advocacy, and more research is needed to shed further l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(70 reference statements)
1
5
0
1
Order By: Relevance
“…This gap can be explained by the influence of external factors on the relationship between the older people and the carer. The carer experiences a conflict of interest balancing the older person's rights to self‐determination against external demands (Vik & Eide, ; Breitholtz et al ., ; Frilund et al ., ; Josse‐Eklund et al ., ). This review and other studies indicate that the home‐care system could benefit from focusing on carers’ scope for a more relational, reflective approach to help instead of focusing on administrative factors (Goethals et al ., ; Mullen, ; Vik & Eide, ; Breitholtz et al ., ; Josse‐Eklund et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This gap can be explained by the influence of external factors on the relationship between the older people and the carer. The carer experiences a conflict of interest balancing the older person's rights to self‐determination against external demands (Vik & Eide, ; Breitholtz et al ., ; Frilund et al ., ; Josse‐Eklund et al ., ). This review and other studies indicate that the home‐care system could benefit from focusing on carers’ scope for a more relational, reflective approach to help instead of focusing on administrative factors (Goethals et al ., ; Mullen, ; Vik & Eide, ; Breitholtz et al ., ; Josse‐Eklund et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten quantitative studies used different instruments to measure nurses' attitude toward patient advocacy. All of these studies consistently reported that nurses, in many different specialties, have positive attitude toward patient advocacy [22,26,[28][29][30][31][32][33][34][35]. In Abbaszadeh et al [34] study, nurses reported they should provide protective nursing advocacy for their patients while Nurse interns believe that patents should be provided interpreter when needed as part of advocacy [36].…”
Section: Resultsmentioning
confidence: 99%
“…Patient advocacy can be influenced by facilitators and barriers. One of the most important facilitators is the nurse-patient relationship [22]. In conclusion, the literature on the definition of nursing advocacy remain ambiguous, contested, and illusive.…”
Section: Active Vs Passive Advocacymentioning
confidence: 99%
“…Patient advocacy in Brazil was proposed as an ethical role of the nurse's professional practice with patients and aims to ensure their rights, contributing to their autonomy. This defense by the nurse can be defined as an intervention to help patients obtain services and benefits that are within their rights, facilitating their care, treatment and well-being (3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%